MASALAH PIDANA MATI DALAM PERSPEKTIF PEMBAHARUAN HUKUM PIDANA DI INDONESIA - Amalia, Mia (Jurnal Wawasan Yuridika, 2012)
If penalty is formulated in the Criminal Code, it will be against the principle of equality. In Netherlands, death penalty has been abolished since 1980. Apart from principle of objection, death penalty occasionally is defended on behalf of religious principle, and moreover the death penalty in Netherlands is not regarded any more to keep and protect legal order. Keywords: principle of equality; death penalty